Improvement of the Shear Strength and Reduction of the Permeability of Sandy Soil using Soybean Crude Urease Calcite Precipitation (SCU-CP) - Erizal; N Annisa, Chika; Putra, Heriansyah; Apriadi (Jurnal Teknik Sipil dan Lingkungan, 2025)
Calcite precipitation is a sustainable soil improvement method because it can increase soil strength and is environmentally friendly. This study aimed to evaluate the use of an innovative soil improvement method, namely soybean crude urease calcite precipitation (SCU-CP), in modifying the strength and permeability of sandy soil. Two types of reagents based on their purity, namely pro analysis (PA) and technical (technical grade), combined with two types of soybeans, namely seeds (conventional) measuring 0.1–0.5 mm and manufactured soybean powder measuring <0.1 mm, were used in this study as the main ingredients in the preparation of calcite. This research was conducted using various tests, including test-tube testing, soil characterization, compressive strength testing (UCS), and permeability testing. The results showed that the variation in reagent purity had no significant effect on the sand soil parameters. Technical and pro-analytical reagents can produce significant soil strength in soils with UCS values >50 kPa and reduce permeability by 50%. Meanwhile, soybean type is an important parameter affecting soil strength in the SCU-CP method. The smaller size of the soybean can lead to a large amount of soybean content in the SCU-CP solution, which affects the disruption of the calcination and bonding process in the soil. This study also showed that the variation in curing time had no significant effect on the soil properties. This study concluded that the particle size of soybean powder is an important factor in the SCU-CP method.